East Asian Arch Psychiatry 2019
DOI: 10.12809/eaap1727
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Factors, and Outcome of Physical Violence against Mental Health Professionals at a Nigerian Psychiatric Hospital

Abstract: Objectives: This cross-sectional study aimed to assess the prevalence, factors, and consequences of physical violence by mentally ill patients against mental health professionals. Methods: 124 of 145 mental health professionals at a Nigerian neuropsychiatric hospital satisfactorily completed a questionnaire on their experiences with physical assault. Results: 77 (62.1%) staff had been assaulted during their whole career; 38 (30.6%) of them were assaulted in the past 12 months. The most common type of assault w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The study’s findings showed statistically significant association with years of employment and likelihood of experiencing physical violence ( p = 0.007). This finding is consistent with the study of Akanni et al ( 2019 ), which revealed that there was an association in having longer years of experience as a nurse and experiencing physical violence. The more experience the nurse had, the more he or she was vulnerable to physical violence.…”
Section: Discussionsupporting
confidence: 93%
“…The study’s findings showed statistically significant association with years of employment and likelihood of experiencing physical violence ( p = 0.007). This finding is consistent with the study of Akanni et al ( 2019 ), which revealed that there was an association in having longer years of experience as a nurse and experiencing physical violence. The more experience the nurse had, the more he or she was vulnerable to physical violence.…”
Section: Discussionsupporting
confidence: 93%
“…In a cross-sectional study carried out in 2020 in Sudan [ 59 ], 50% of doctors reported they had been victims of some form of violence (mainly verbal violence and, as for other countries, among younger doctors). A Nigerian study showed similar findings among physicians in general [ 60 ] while the prevalence of physical violence against mental health professionals showed that 33% of the doctors report physical assaults in the previous 12 months and 73% in their whole career [ 61 ]. Slightly lower but still significant figures were reported in Botswana [ 62 ].…”
Section: Resultsmentioning
confidence: 86%
“…A total of 22 peer reviewed research studies met the inclusion criteria and were included in this review on workplace violence among healthcare workers in Africa (See Table 1). Nineteen out of the twenty-two studies employed a cross-sectional study design (Abdellah and Salama, 2017;Samir et al, 2012;Yenealem et al, 2019;Azodo et al, 2011;Abou-ElWafa et al, 2015;Abodunrin et al, 2014;Boafo, 2016;Olashore et al, 2018;Boafo and Hancock, 2017;Tiruneh et al, 2016;Seun-Fadipe et al, 2019;Sethole et al, 2019;Muzembo et al, 2015;Amkongo et al, 2019;Ogundipe et al, 2013;Boafo, 2018;Banda et al, 2016;Ukpong et al, 2011;Akanni et al, 2019). Two studies employed mixed method (Kennedy and Julie, 2013;Sisawo et al, 2017), while one used ethno-phenomenological design (Khalil, 2009).…”
Section: Characteristics Of the Reviewed Studiesmentioning
confidence: 99%